Transferable Living Unit: Prototype Housing for the Transient - Jay Siebenmorgen (Oz, 2003)
In future societies, what will it mean to dwell? Globalization is changing the way we engage the world. We are in a culture that is increasingly fixated on speed, efficiency, and the accessibilities of information exchange.